Factors Associated With Regular Exercise Participation in Individuals With Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Ja Yun Choi; Sola Cho; Su Yeon Lim; Sehyun Cho (Journal of Gerontological Nursing, 2026)
Purpose: Although exercise is central to chronic obstructive pulmonary disease (COPD) management, participation remains low. The current review identified factors influencing exercise participation. Method: International (MEDLINE, EMBASE, and Cochrane CENTRAL) and Korean (Korean Studies Information Service System and Korea Institute of Science and Technology Information) databases were searched for studies published between 2013 and 2024. Two reviewers independently conducted study selection, data extraction, and quality appraisal. Results: Of 22 studies, 21 were of high quality and one of moderate quality. Motivation ( r = 0.15, p = .035), symptoms ( r = −0.14, p = .015), educational level ( r = 0.13, p = .003), pulmonary function ( r = 0.09, p = .049), and social support ( r = 0.05, p = .040) were associated with exercise in COPD; heterogeneity was significant only for symptoms (I 2 = 89.3%, p < .001). Conclusion: Exercise engagement is multifaceted, reflecting the interplay of individual, clinical, and social factors. These findings provide evidence informing the development of targeted interventions that promote sustained exercise engagement.